Environmental applications of nanomaterials synthesis, sorbents and sensors - Fryxell, Glen E.; Cao, Guozhong (Imperial College Press, 2007)
This volume is concerned with functional nanomaterials: materials containing specific, predictable nanostructure whose chemical composition or interfacial structure enable them to perform a specific job ? destroy, sequester or detect some material that constitutes an environmental threat. Nanomaterials have a number of features that make them ideally suited for this job: high surface area, high reactivity, easy dispersability, and rapid diffusion. The purpose of this book is to showcase how these features can be tailored to address some of the environmental remediation and sensing/detection pr.
Keywords: Nanostructured materials -- Environmental aspects.; Pollutants.; elektronické knihy; electronic books